2023
DOI: 10.3390/cells12182317
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Regulatory T Cells in the Meninges and Spinal Cord of Male and Female Mice with Neuropathic Pain

Nathan T. Fiore,
Brooke A. Keating,
Yuting Chen
et al.

Abstract: Immune cells play a critical role in promoting neuroinflammation and the development of neuropathic pain. However, some subsets of immune cells are essential for pain resolution. Among them are regulatory T cells (Tregs), a specialised subpopulation of T cells that limit excessive immune responses and preserve immune homeostasis. In this study, we utilised intrathecal adoptive transfer of activated Tregs in male and female mice after peripheral nerve injury to investigate Treg migration and whether Treg-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Controversially, Tregs can either inhibit the inflammation [ 44 ], or stimulate the progression of bone cancer pain (unpublished data in our research group). Nathan et al [ 45 ] reported different changes in meningeal and lymph node immune cell profiles between male and female mice. Inflammation is a process influenced by metabolism [ 46 , 47 ], and we therefore speculated that the different functions of Tregs may be attributed to the metabolic mode.…”
Section: Discussionmentioning
confidence: 99%
“…Controversially, Tregs can either inhibit the inflammation [ 44 ], or stimulate the progression of bone cancer pain (unpublished data in our research group). Nathan et al [ 45 ] reported different changes in meningeal and lymph node immune cell profiles between male and female mice. Inflammation is a process influenced by metabolism [ 46 , 47 ], and we therefore speculated that the different functions of Tregs may be attributed to the metabolic mode.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 It is well known that microglia are closely involved in neuropathic pain in male mice, whereas the neuropathic pain in female mice does not require microglia, but adaptive immune cells such as T lymphocytes to produce the same pain. [62][63][64] On the other hand, in studies of pain in female animals, it is necessary to keep the sex cycle of all female animals constant because estrogen is often involved. 65,66 In addition, there have been several studies that have examined the relationship between IFN-γ and pain, and it is necessary to compare the results of these studies with those of this study, but all of these studies used male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Treg treatment also modulates the amount of reactive astrocytes of different phenotypes to reduce neurotoxicity by attenuating astrocyte GFAP expression. Interestingly this therapeutic effect of Treg cells manifests itself differently in female and male mice, with a reduction in the number of neurotoxic astrocytes in peripherally injured male mice, and conversely, in peripherally injured females, the number of protective astrocytes was increased with peripheral nerve injury ( 135 ). Brain Treg cells inhibit neurotoxic astrocyte proliferation and protect neurons from damage by producing the low-affinity EGFR ligand AREG ( 136 ).…”
Section: Regulatory Role Of Treg Cells In Scimentioning
confidence: 99%